Assessing the interspecies and intraspecies diversity of Cas1 and Cas3 proteins of the CRISPR-Cas system in vibrio cholera and Escherichia coli strains - Tabassum, Tahani; Shahriar, Sagarika (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2021.